Ergometric and physiological characteristics of special physical fitness of athletes in sports with endurance - Diachenko, A.; Shkrebtii, Y.; Chenging, Y. (Slobozhanskyi herald of science and sport, 2021)
Purpose: to determine the individual parameters of the training work modes on the rowing ergometer for the development of specific components of the functional support of athletes in sports with the manifestation of endurance.